BANKING SERVICE ORIENTATION MODEL IN STRATEGIC HRM AND SYSTEM DYNAMICS PERSPECTIVE - Audia Junita; Ferdinand D. Saragih; Andreo Wahyudi Atmoko (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2019)
This paper seeks to explore a model of banking service orientation in strategic human resource management and system dynamic perspective, theoretically. As a scientific effort to develop a study of strategic human resource management. So far, the relationship between elements in strategic human resource management perspective as a system is only analyzed linearly. This article is the result of a literature study. An analysis is done narratively, to answer research problems. Research finding in the form of banking service-orientation model in strategic human resource management and system dynamic perspective, that illustrates the interaction between marketing differentiation strategy, commitment-based human resource system, service-oriented role behaviors to achieve banking performance.